Influencing Factors on Housing Purchase Decisions: Promotion, Product Quality, and Price: Faktor-faktor yang Mempengaruhi Keputusan Pembelian Rumah: Promosi, Kualitas Produk, dan Harga - Yanti, Isma Dwi; Astuti, Mudji (Indonesian Journal of Law and Economics Review, 2023)
This quantitative research investigates the impact of promotion, product quality, and price on housing purchase decisions. Employing a non-probability simple sampling method, 80 respondents from a consumer base were surveyed, and data were analyzed using multiple linear regression analysis, classical assumption tests, t-tests, F-tests, multiple correlation coefficients, and R2 calculations in SPSS version 25.0. The findings demonstrate that promotion, product quality, and price individually influence purchasing decisions. Moreover, when considered collectively, these factors significantly affect housing purchase decisions. This study provides valuable insights for marketers and practitioners seeking to optimize their strategies in the housing industry. Highlights: Multiple Linear Regression: Employed statistical analysis to quantify the influence of promotion, product quality, and price on housing purchase decisions. Individual and Collective Impact: Revealed the separate effects of each factor and their combined significance in shaping consumer choices. Marketing Strategy Insights: Offers actionable insights for housing industry practitioners to enhance their marketing strategies based on empirical evidence. Keywords: Housing Purchase, Promotion, Product Quality, Price, Consumer Decision